Anticancer drug release from poly(N-isopropylacrylamide/itaconic acid) copolymeric hydrogels - KAYAMAN APOHAN, NİLHAN (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
The drug uptake and release of anticancer drug from N-isopropylacrylamide/itaconic acid copolymeric hydrogels containing 0-3 mol% of itaconic acid irradiated at 48 kGy have been investigated. 5-Fluorouracil (5-FU) is used as a model anticancer drug. The effect of 5-FU solution on swelling characteristics of PNIPAArn and P(NIPAAm/IA) copolymeric hydrogels have also been studied. The percent swelling, equilibrium swelling, equilibrium water/5-FU content and diffusion constant values are evaluated for poly(N-isopropylacrylamide) (PNIPAAm) and poly(N-isopropylacrylamide/itaconic) (P(NIPAAm/IA)) hydrogels at 130 ppm of 5-FU solution at room temperature. Diffusion of 5-FU solution into the hydrogels has been found to be the non-Fickian type. Finally, the kinetics of drug release from the hydrogels are examined. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: hydrogel; N-isopropylacrylamide; itaconic acid; 5-fluorouracil; drug release; DIFFUSION; WATER